Information Quality and Decisions of Online Drivers to Participate in BPJS Health Insurance - Adila Solida; Ardiyansyah (International Journal of Medicine and Health, 2024)
The information quality is an important factor in influencing someone's decision, including online drivers. In Jambi City, some people affected by the Covid-19 pandemic chose to change professions to become online drivers due to disruption to the household economy. Undertaking this profession, online drivers are at risk of contracting diseases and safety and health hazards while working, while there are still those who do not have health insurance to face these risks. The aim of this research is to analyze the influence of information quality on the decision to participate in BPJS Health insurance for online drivers in Jambi City. A quantitative study approach with a cross-sectional design was carried out in Jambi City in 2023. There were 96 respondents selected based on accidental sampling techniques. The study instrument is a questionnaire. Data analysis used the chi-square test. There is a significant influence between the factors accuracy (p=0.001), timeliness (0.000), relevance (p=0.001), and completeness of information on the decision to participate in BPJS Health insurance for online drivers. It is recommended that BPJS Health increase its educational campaign about the benefits of health insurance and improving the quality of timely and relevant information.